A model for the introduction of jazz into the South African secondary music education curriculum - Van Vuuren, Tessaleigh (University of the Free State, 2000)
It has been found that there exists a definite lack of suitable, comprehensive teaching models which include both a detailed learning content for jazz and a plan or method for successfully presenting this content to secondary school learners. This research therefore aims to develop a suitable model for the presentation of jazz in secondary music education. The proposed model consists of two parts. In the first part (Chapters 2 to 7) research is undertaken to determine the learning content to be used in the model. It provides the teacher with a single, comprehensive and detailed source on jazz, illustrated with relevant transparency masters and music examples. An extensive historical perspective of jazz is provided. This includes an explanation of the term and the concept of jazz as well as a fairly thorough discussion of the geographically-based aspects and the different types of music which gave rise to jazz. All the different styles jazz went through during the course of its history are indicated. Each style is discussed more or less with regard to its structure and/or characteristics, exponents and instrumental ensembles. The various elements that constitute and shape the structure of jazz are dealt with. The life and music of the most prominent jazz instrumentalists are discussed. In addition, the more prominent male and female jazz vocalists also receive attention. The (essential and optional) musical instruments found in jazz groups are dealt with. They are discussed more or less with regard to what each instrument looks like, its sound, compass, perhaps a brief history and some playing techniques, and its use during the course of jazz history. Large and small instrumental jazz groups are discussed more or less with regard to the construction of the groups, their historical development and the various bands and combos that existed during the course of jazz history. In the second part of the model (Chapter 8) a plan or method is decided on with which to best present the learning content of jazz, presented in the first part of the model, to secondary school learners. Firstly, the learning content is systemised into a logical, more manageable modular system of six modules, each of which is divided into a number of teaching units or lessons. Secondly, the didactic situation in which the model would find expression is introduced. Thirdly, potentially suitable lesson plans from a variety of literature are investigated to determine a general framework and guidelines (criteria) for a pedagogically- and didactically-sound lesson plan, which is also scientifically and theoretically grounded. Finally, an example of a worked-out (demonstration) lesson, using the learning content presented in part one of the model, is provided. It forms a guideline for the presentation of the other lessons. Jazz is slowly gaining more prominence in the South African music culture. Overt public support for it is growing, and it is increasingly being accepted among adults. In order to extend its popularity, jazz needs to be incorporated into the South African (secondary) music education curriculum, preferably by means of the systematic exposition thereof in well-designed programmes or models. Such a model is presented in this study.

Dit is bevind dat daar 'n definitiewe behoefte is aan geskikte, omvattende onderrigmodelle wat beide 'n gedetailleerde leerstof vir jazz en 'n plan of metode vir die suksesvolle aanbieding vir hierdie leerstof aan sekondêre skool leerders insluit. Die navorsing het daarom ten doelom 'n geskikte model vir die aanbieding van jazz in sekondêre musiekonderrig te ontwikkel. Die voorgestelde model bestaan uit twee dele. In deel een (Hoofstukke 2 tot 7) word navorsing gedoen om die leerstof wat in die model gebruik gaan word, te bepaal. Dit voorsien die onderwyser van 'n enkele, omvattende en gedetailleerde bron ten opsigte van jazz. Die inligting word geïllustreer met relevante transparantmeesters en musiekvoorbeelde. 'n Uitgebreide historiese perspektief oor jazz word verskaf. Dit sluit in 'n verduideliking van die term en begrip sowel as 'n redelik deeglike bespreking van die geografies-gebaseerde aspekte en verskillende tipes musiek wat aanleiding gegee het tot die ontwikkeling van jazz. Die verskillende style waardeur jazz ontwikkel het word aangedui. Elke styl word bespreek min of meer ten opsigte van die struktuur en/of eienskappe daarvan, verteenwoordigende musikante en instrumentale ensembles. Die verskeie elemente wat bygedra het tot die (vorming van die) struktuur van jazz word behandel. Die lewe en musiek van die mees prominente jazz instrumentaliste word bespreek. Die meer prominente jazz sangers en sangeresse word ook bestudeer. Die (noodsaaklike en opsionele) musiekinstrumente wat in jazz groepe aangetref word, word behandel. Die instrumente word bespreek min of meer ten opsigte van hoe die instrument lyk, die klank en omvang daarvan, moontlik 'n kort agtergrond en enkele speeltegnieke, asook die gebruik daarvan deur die historiese verloop van jazz. Groot en klein instrumentale jazz-groepe word bespreek min of meer ten opsigte van die samestelling van die groepe, hulle historiese ontwikkeling en die verskeie groot en klein groepe wat deur die historiese verloop van jazz bestaan het. In deel twee (Hoofstuk 8) word daar op 'n plan of metode besluit waarmee die leerstof vir jazz - aangedui in die eerste deel van die model - op die mees doeltreffende wyse aan sekondêre skool leerders aangebied kan word. Eerstens word die leerstof gesistematiseer in 'n meer logiese, meer hanteerbare modulêre sisteem, bestaande uit ses modules; elkeen van die modules is in 'n aantal onderrigeenhede of lesse verdeel. Tweedens word die didaktiese situasie waarin die model gaan neerslag vind, bekendgestel. Derdens word potensieel geskikte lesplanne vanuit 'n wye literatuurveld bestudeer om 'n algemene raamwerk en riglyne (kriteria) vir 'n pedagogies-didakties verantwoordbare lesplan, wat ook wetenskaplik en teoreties gefundeerd is, daar te stel. Laastens word 'n voorbeeld van 'n uitgewerkte (demonstrasie-) les, wat gebruik maak van die leerstof aangebied in deel een van die model, verskaf. Dit vorm 'n riglyn vir die aanbieding van die ander lesse. Jazz is stadig maar seker besig om 'n meer prominente posisie in die Suid- Afrikaanse musiekkultuur in te neem. Openbare ondersteuning daarvoor is aan die toeneem en dit word al hoe meer deur volwassenes aanvaar. Om die gewildheid van jazz nog verder te laat uitbrei, is dit nodig om die musiek in die Suid-Afrikaanse (sekondêre) musiekonderrigkurrikulum te inkorporeer, verkieslik met behulp .van die sistematiese eksposisie daarvan in goed beplande programme of modelle. So 'n model word in hierdie studie aangebied.
Dissertation (M.Mus. (Music))--University of the Free State, 2000
Keywords: Music; Music education; Class music; Music at secondary school; Jazz; Jazz education; Teaching jazz; Jazz at secondary school; Jazz model; Jazz history; Education -- Curricula